Las finalidades de la educación / [Ángel I. Perez Gómez ; presentación José Torreblanca] - Torreblanca, José (Torreblanca Prieto); Pérez Gómez, Ángel I. (Cuadernos "Colectivo Lorenzo Luzuriaga" ; 1)
En cub.: Curso: Los fines de la educación